2011
DOI: 10.1080/01431161.2011.581709
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change on sea level rise in Lagos, Nigeria

Abstract: Sea level rise and ocean surge are the major potential impacts of climate change in the rapidly growing urban Lagos in Nigeria. Coastal inundation is, however, expected to increase problems of flooding and intrusion of sea water into freshwater sources and ecosystems, thereby heightening the social conflict already prevalent in this area. This article examines the historical trend in the coastal extent of one of the most populous coastal cities in the tropics and projects the potential impact on coastline chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 18 publications
(7 reference statements)
0
10
0
Order By: Relevance
“…Climate change impacts may vary depending on micro-climates in particular areas. Sea level rise, inundation and typhoons have been found to have a big impact on coastal and low-elevation deltas (Fashae & Onafeso, 2011;Ghodrati, Alemi Safaval, & Lashteh Neshaei, 2016;Goharnejad, Shamsai, & Hosseini, 2013) while the effects of temperature and rainfall variations pose high risks to mountainous areas (Bhatti, Koike, & Shrestha, 2016;Briner, Elkin, & Huber, 2013;Pina Poujol, 2013). In the following part of this study the author examines the level of impact of climate change to the tourism sector in the region from three principal stakeholders' perspectives: tourism authorities, tourism business and tourists.…”
Section: Level Of Climate Change Impacts To Tourism Sector In the Mekmentioning
confidence: 99%
“…Climate change impacts may vary depending on micro-climates in particular areas. Sea level rise, inundation and typhoons have been found to have a big impact on coastal and low-elevation deltas (Fashae & Onafeso, 2011;Ghodrati, Alemi Safaval, & Lashteh Neshaei, 2016;Goharnejad, Shamsai, & Hosseini, 2013) while the effects of temperature and rainfall variations pose high risks to mountainous areas (Bhatti, Koike, & Shrestha, 2016;Briner, Elkin, & Huber, 2013;Pina Poujol, 2013). In the following part of this study the author examines the level of impact of climate change to the tourism sector in the region from three principal stakeholders' perspectives: tourism authorities, tourism business and tourists.…”
Section: Level Of Climate Change Impacts To Tourism Sector In the Mekmentioning
confidence: 99%
“…Other studies on impact of sea level rise on coastal communities in Nigeria included those of [17,18,19,20,21,22,23]. However, most of these studies were either too generalized or do not cover the current study area.…”
Section: Brief Review Of Previous Researchmentioning
confidence: 99%
“…Based on photographic evidence and comparison with satellite imagery, coastlines in some urban areas in the Gulf of Guinea seem to have been retreating over the past few decades (Dossou and Glehouenou-Dossou 2007;Fashae and Onafeso 2011). Ericson et al (2006) found that sediment trapping is the dominant cause of contemporary effective sea level rise for the Niger delta, with contributions from land subsidence due to oil exploration.…”
Section: Impact Detectionmentioning
confidence: 99%